Evaluation of Laboratory Findings in Combined Iron-Vitamin B12 Deficiency Anemia - محمود, محمد; روز سعيد ,; فراس حسين, (Latakia University Journal -Medical Sciences Series, 2023)
Introduction: Anemia is one of the most common health problems in the world. Micronutrient deficiency anemia (iron, folic acid, vitamin B12 and vitamin A) is the most common cause of anemia in developing countries. Deficiencies of more than one element are common in gastrointestinal diseases and malnutrition. Iron-deficiency anemia combined with vitaminB12 deficiency may mask the typical hematological picture of megaloblastic anemia and pose a problem in diagnosis. This research aimed to study the effect of deficiency association on laboratory findings and to evaluate the use of some indicators in predicting the incidence of vitamin B12 deficiency in patients with IDA. Materials and Methods: The study included 85 anemic patients, including 35 IDA patients, 25 vitamin B12 deficiency patients, and 25 patients with mixed anemia, in addition to 35 healthy controls. Venous blood samples were drawn for complete blood count analysis, peripheral blood film, and reticulocyte ratio, as well as serum titer of vitamin B12, ferritin, LDH activity, and serum bilirubin. The medians of these tests were compared between the four study groups to identify statistically significant differences, and using ROC curves, the sensitivity and specificity of the cut off values for some tests were calculated to aid in diagnosis. Results: The predominant picture when IDA was associated with vitamin B12 deficiency anemia was microcytosis with hypochromia with a decrease in the number of platelets compared to IDA group. Examination of peripheral blood showed hypersegmentation in 60% of combined anemia patients, which is slightly less frequent than that of vitamin B12 deficiency anemia group. It also showed dimorphic assets (Macro-ovalocytes and microcytes) in most cases. The average activity of LDH and the concentration of indirect bilirubin were significantly higher in vitamin B12 deficiency and mixed anemia groups than in IDA group while Reticulocytes percentage was lower. Conclusion: Absolute reticulocyte count, together with LDH and serum bilirubin, are important diagnostic tests to infer the presence of vitamin B12 deficiency anemia associated with IDA when the general appearance is microcytic and hypochromic.